2012
DOI: 10.2147/ndt.s38450
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between severity of obsessive-compulsive symptoms and schizotypy in obsessive-compulsive disorder

Abstract: PurposeObsessive-compulsive disorder (OCD) patients exhibit a noninhibition response pattern very similar to that observed in schizotypy patients in cognitive tasks. It has been suggested that the reduced cognitive inhibition observed in both schizotypy and OCD may result in the frequent entry into awareness of unacceptable urges and intrusive thoughts. The aim of this study was to investigate the relationship between the severity of obsession or compulsion and schizotypy in OCD.Patients and methodsSixty subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
(18 reference statements)
2
5
0
1
Order By: Relevance
“…First of all, we explored the relationship of schizotypal traits with several variables including the duration and severity of OCD, anxiety levels, childhood abuse and neglect. In consistent with some previous studies [4][5][6]8,12,15 , our results demonstrated that positive and disorganized schizotypal traits were signicifantly related to the current OCD severity. We have also found that current anxiety scores may interact between schizotypal symptoms and the current OCD severity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…First of all, we explored the relationship of schizotypal traits with several variables including the duration and severity of OCD, anxiety levels, childhood abuse and neglect. In consistent with some previous studies [4][5][6]8,12,15 , our results demonstrated that positive and disorganized schizotypal traits were signicifantly related to the current OCD severity. We have also found that current anxiety scores may interact between schizotypal symptoms and the current OCD severity.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies demonstrated a link between positive symptoms of schizotypy (magical thinking, unusual perceptual experiences, ideas of reference, paranoid ideations) and OCS 6,8,12 . These patients with OCD and positive symptoms of schizotypy have been found to have more severe OCD symptoms [12][13][14] , more prominent obsessions 14,15 , a poorer prognosis 13 and an earlier age of onset of their disorder 2,16 . OCD and high-schizotypy has also been associated with specific OCD symptoms such as checking, counting, ordering/arranging, and hoarding 2,3,5 .…”
mentioning
confidence: 99%
“…Consistent with findings in the literature thus far (Chmielewski and Watson, 2008; Tallis and Shaffran, 1997; Yamamoto et al, 2012), there were conflicting findings between results derived from self-report and clinician-administered instruments in relation to the association between high levels of schizotypy and specific OCD symptoms. The self-report instrument (the VOCI) revealed associations with more OCD symptoms than did the clinician-administered instrument (the Y-BOCS), possibly because self-report measures tend to overestimate symptoms (Rush et al, 2006).…”
Section: Discussionsupporting
confidence: 77%
“…The relationship between OCD-HS and specific OCD symptoms is somewhat unclear. Some studies (Tallis and Shaffran, 1997; Yamamoto et al, 2012) have associated OCD-HS with more prominent obsessions as measured by the Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) (Goodman et al, 1989), in contrast to findings of one other study (Poyurovsky et al, 2008). OCD-HS has also been associated with specific OCD symptoms such as checking (Aardema and Wu, 2011; Chmielewski and Watson, 2008), ordering (Chmielewski and Watson, 2008; Sobin et al, 2000) and hoarding (Aardema and Wu, 2011; Chmielewski and Watson, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, OCD patients with SPD/SPTs exhibited higher rates of autogenous, sexual, religious, and order/symmetry obsessions, 31,37,41,52 and higher levels of ordering/arranging, counting, and checking compulsions. 37,81 They also showed increased severity of OCSs 44,45 and greater behavioral compulsivity in general. 34 Noteworthy, higher levels of schizotypal features appeared to be associated to compulsive hoarding, 41,51 especially in women, 31,54,69,78 and to body dysmorphic disorder.…”
Section: Clinical and Psychopathological Correlates Of Ocd-spd Comorbiditymentioning
confidence: 95%